2016
DOI: 10.1007/s10993-015-9390-y
|View full text |Cite
|
Sign up to set email alerts
|

Transnational English language learners fighting on an unlevel playing field: high school exit exams, accommodations, and ESL status

Abstract: Though previous research addresses the negative impact of state-mandated high school exit exams on English language learners' (ELLs) educational experiences, less attention has been given to how college-oriented ELLs, especially those who attended school in their home countries before coming to the US, handle rigorous exams or gain access to tertiary education. This paper examines how lateentrant transnational ELL students negotiate the linguistic and academic challenges imposed by high school exit exams. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The academic challenges faced by the students mirror findings of research that document the range of tests international secondary students encounter (e.g., Alexander, 2017;Gan, 2009;Kim & Okazaki, 2014) and demonstrate the important role of perceived competence in the wellbeing of international students (e.g., Kuo & Roysircar, 2006;Leung, 2001).…”
Section: Special World: Testsmentioning
confidence: 61%
See 1 more Smart Citation
“…The academic challenges faced by the students mirror findings of research that document the range of tests international secondary students encounter (e.g., Alexander, 2017;Gan, 2009;Kim & Okazaki, 2014) and demonstrate the important role of perceived competence in the wellbeing of international students (e.g., Kuo & Roysircar, 2006;Leung, 2001).…”
Section: Special World: Testsmentioning
confidence: 61%
“…International students often struggle to make friends with host nation students (Gan, 2009;Kim & Okazaki, 2014). Reasons for this include cultural dissonance (Alexander, 2017;Gan, 2009), language difficulties (Kuo, 2011) and perceptions of discrimination (Kuo & Roysircar, 2006). These obstacles to developing friendships mean that most international students form their closest relationships with other overseas students (Hendrickson et al, 2011;McFaul, 2016;Rienties et al, 2013).…”
Section: Special World: Alliesmentioning
confidence: 99%
“…Adolescents across various studies have identified the role of ELP testing in their classification as ELs (e.g., Alexander, 2017; Koyama, 2004; McKay & Wong, 1996; Menken, 2008; Valenzuela, 1999). Within this research, they not only describe the function of these tests, but they often share their opinions about ELP testing.…”
Section: Routine El Practices: Elp Testing and El‐related Course Plac...mentioning
confidence: 99%
“…It emphasizes that both educators and students have the authority to make decisions. This study highlights the significance of providing equal treatment for ELLs and discusses important concerns of reliability of tests and equity in US language education regulations [11].…”
Section: Introductionmentioning
confidence: 95%